Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jcla.22272
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of serum bilirubin in stage IV colorectal cancer patients

Abstract: Pre-treatment elevated TBIL and DBIL levels were associated with poor OS in stage IV CRC patients. Moreover, DBIL could be considered as an independent prognostic biomarker for OS. Furthermore, DBIL had similar prognostic efficacy as CEA for OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In the right-sided colon group, the time-dependent ROC curve of the albumin-NLR was superior to the mGPS and SIS starting at the 16th month after surgery, and the AUC of the albumin-NLR for OS ranged from 0.579 to 0.669 since then. Although the AUC of the albumin-NLR in our study was less than 0.7, it was in accordance with the AUC of the classic prognostic factors reported for CRC patients, such as CEA [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the right-sided colon group, the time-dependent ROC curve of the albumin-NLR was superior to the mGPS and SIS starting at the 16th month after surgery, and the AUC of the albumin-NLR for OS ranged from 0.579 to 0.669 since then. Although the AUC of the albumin-NLR in our study was less than 0.7, it was in accordance with the AUC of the classic prognostic factors reported for CRC patients, such as CEA [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…Zhang et al found that high DBIL level was an independent prognostic factor for OS and DFS, and a higher proportion of lymph node metastasis and lymphovascular invasion was observed at higher DBIL levels than at lower DBIL levels [10]. Yang et al also found that in stage IV CRC patients, elevated levels of TBIL and DBIL were associated with poor OS [20]. DBIL can be considered an independent prognostic biomarker of OS, and the prognostic effect of DBIL on OS is similar to that of carcinoembryonic antigen (CEA).…”
Section: Discussionmentioning
confidence: 99%
“…Bilirubin has been reported to possess important antioxidant and anticancer functions and was considered as an efficient prognostic biomarker for overall survival in advanced CRC [ 23 , 24 ]. Lower plasma bilirubin levels were found in CRC compared to healthy controls [ 19 ].…”
Section: Discussionmentioning
confidence: 99%